Organized Illegal Migration as Manifestation of Transnational Criminality and Source of Threats to National Security of Ukraine (Bulletin of Kharkiv National University of Internal Affairs, 2021)
Illegal migration is publicly dangerous, harmful, criminal phenomenon, which really threatens to national security of many countries. The issue of providing the proper state of national security is of greater actuality for Ukraine. Therefore, the issues of scientific analysis of the relationship of migration and national security, making suggestions for the improvement of counteraction to illegal migration, taking into account the threats which it creates, are very important.The problem of the organized illegal migration of population is studied by experts as one that requires an urgent solution. The indicated form of migration was transformed into highly profitable criminal business, became the important element of the transnational organized crime. The latter has already gone beyond the interests of national security, since it threatens to political stability and economic development of many world countries, it results in serious violations of human rights, development of parallel economy, which feeds crime.The relevance of the problem of the organized illegal migration predetermines the increased attention to it both by separate countries and at international level, requires urgent development and introduction of new effective measures of counteraction. Aggression of the Russian Federation and caused mass internal moving of population in our country, Ukraine’s approaching to the EU and introduction of the visa-free arrangements with most Member States of the EU stipulated the cardinal change of approaches in regulating migration processes, transition from repressive methods to prevention.Therefore the present system of counteraction to the organized illegal migration requires an improvement by effective application of administrative measures to illegal migrants in combination with bringing their traffickers to criminal liability and other measures of migratory sphere’s regulation. Thus, granting priority to national interests in the state migration policy at the admissible restriction of human right to free movement is very important.